Functional Effects of Vegetation on the Radiant Energy Budget of Boreal Forest - Haag, Richard W.; Bliss, L. C. (Canadian Geotechnical Journal, 1974)
In contrast to tundras, where the mass of vegetation is low and its effect on energy exchange relatively small, boreal forest vegetation exerts a more important buffering effect on energy flux to and from the ground surface. Air movement below the canopy is reduced, and a relatively high proportion of solar radiation is absorbed by the canopy directly, to be lost as sensible or latent heat. Removal of the buffer provided by stratified vegetation results in increased soil heat flux and ground temperatures, and increased depth of the active layer, which in areas of ice rich permafrost can lead to surface subsidence.